Improvement of the traction current asymmetry control system - Basharkin, Maksim V.; Isaycheva, Alevtina G.; Teplyakov, Valery B. (Nexo Revista Científica, 2021)
The article presents approaches that allow modernizing the system for monitoring the asymmetry of the traction current. The existing systems of technical diagnostics and monitoring of the technical condition of automation and telemetry control devices, which have found wide application on the railways of JSC Russian Railways, do not allow monitoring the condition of adjacent railway transport infrastructure systems that affect the performance of railway automation and telemetry control devices. Besides, information about the condition of the object being diagnosed is sent to the monitoring center, while the operational and repair personnel do not have the necessary information and start working only after receiving information about the malfunction from the dispatcher of the monitoring center. The mobile device, proposed in the article, allows reducing the time necessary for obtaining information about the unserviceable condition of the railroad line. The article presents the analysis of gadgets planned for use in a mobile device, and the concept of the interface of the mobile application for technicians. It is noted that the hardware intended for use in a mobile device must provide protection against unauthorized access to the application, as well as have a high degree of protection against penetration. Besides, the article identifies the areas for further improvement of the traction current asymmetry control system.